2018
DOI: 10.1021/acsami.7b19457
|View full text |Cite
|
Sign up to set email alerts
|

NiOOH Exfoliation-Free Nickel Octahedra as Highly Active and Durable Electrocatalysts Toward the Oxygen Evolution Reaction in an Alkaline Electrolyte

Abstract: A layered β-NiOOH crystal with undercoordinated facets is an active and economically viable nonnoble catalyst for the oxygen evolution reaction (OER) in alkaline electrolytes. However, it is extremely difficult to enclose the β-NiOOH crystal with undercoordinated facets because of its inevitable crystal transformation to γ-NiOOH, resulting in the exfoliation of the catalytic surfaces. Herein, we demonstrate {111}-faceted Ni octahedra as the parent substrates whose surfaces are easily transformed to catalytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 69 publications
4
68
0
Order By: Relevance
“…4 It is likely that the surface of m-NiO is covered with both b-NiOOH and g-NiOOH, which form during the water oxidation process, and a-Ni(OH) 2 and b-Ni(OH) 2 during the reverse scan. 39,40 This may clarify the changes in the CV curves over multiple cycles (see Fig. S4 †).…”
Section: Resultsmentioning
confidence: 90%
“…4 It is likely that the surface of m-NiO is covered with both b-NiOOH and g-NiOOH, which form during the water oxidation process, and a-Ni(OH) 2 and b-Ni(OH) 2 during the reverse scan. 39,40 This may clarify the changes in the CV curves over multiple cycles (see Fig. S4 †).…”
Section: Resultsmentioning
confidence: 90%
“…Recently, it has been reported that non‐precious‐metal nanomaterials can be used as the potential alternative catalysts for HER or OER . For example, Ni‐based sulfides and phosphides were synthesized for the electrocatalytic HER, and Ni‐based oxides and hydroxides exhibited electrochemical oxygen evolution activities . Since the overall water splitting is critical in the practical application, it is desired to develop bifunctional electrocatalysts .…”
Section: Figurementioning
confidence: 99%
“…Modifications of nickel (oxy)hydroxide catalysts to boost OER performance are mainly focusedo n enhancing the intrinsic activity,e xposing more active sites and promoting charget ransfer by heteroatom doping as well as designing and fabricating highly efficient nanostructures/nanocomposites of the catalysts. [28] Heteroatomic Fe-doping in nickel-based (oxy)hydroxide was demonstrated as one of the most promising methods to improve the OER activity.B oettcher and co-workersf ound that the intentional and/or incidental incorporation of Fe improved the catalytic activityo fn ickel (oxy)hydroxide significantly (Figure 3a and b). They demonstrated that the introductionofF eaffects the NiOOH electronic structure and exerts ap artial-charge transfera ctivation on Ni.…”
Section: Nickel (Oxy)hydroxide-based Electrocatalystsmentioning
confidence: 99%